The Analysis of Facial Anthropometry Based on the Facial Index Between Acehnese and Minangnese Ethnic Groups Among Medical Students at Syiah Kuala University - Kamilia, Afina; Waraztuty, Ika; Amirsyah, Mirnasari; Maulana, Reza; Rizal, Syamsul (Lumbung Pare Cendekia, 2024)
The human face is one of the most dominant parts of the body used to distinguish identities. Facial shape is influenced by gender, race, ethnicity, climate, socioeconomic status, nutrition, and genetic factors. To determine an individual's facial type, facial anthropometric measurements can be conducted. Facial anthropometry is a discipline that measures and analyzes human facial proportions, providing essential information about the differences in shape and size among various races, ages, and genders. Once facial anthropometric data is obtained, one can determine a person's facial type using the facial index formula. The facial index is the ratio of facial height to facial width, multiplied by 100. This research was conducted at the Faculty of Medicine, Syiah Kuala University, with a total of 64 research subjects, consisting of 32 Acehnese individuals and 32 Minangnese individuals who met the inclusion criteria on August 30, 2023. This study is descriptive-analytic with univariate analysis. The results of this study indicate that the facial type of Acehnese individuals is leptoprosopic, with 14 individuals (43.75%), while the facial type of Minangnese individuals is also leptoprosopic, with 13 individuals (40.6%).